2020
DOI: 10.25134/erjee.v9i1.3785
|View full text |Cite
|
Sign up to set email alerts
|

A study on students' needs in learning English for pharmacy (A starting point to design innovative syllabus)

Abstract: This study aims to discover the needs of pharmacy students as an input to design an ESP syllabus. The needs analyses were conducted by distributing questionnaires to and interviewing the respondents. The responses were analyzed based on a comprehensive concept of need analysis proposed by Dudley-Evans and St. John. The findings showed that most students consider themselves poor in vocabulary and weak in speaking, listening, writing, and pronunciation. Hence, it is crucial to improve their skills to enable them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The research implied that the course fit ESP learning in the pharmacy department. Other research reported the vast challenges in teaching English to pharmacy students, from the teachers' knowledge gap in the pharmaceutical field, big classes, and students' lack of English ability and resources (Solihati & Rahayu, 2020). The research also stated that students mostly learn in middle school and extensively try to improve their English skills independently from various sources.…”
Section: A Related Researchmentioning
confidence: 94%
See 2 more Smart Citations
“…The research implied that the course fit ESP learning in the pharmacy department. Other research reported the vast challenges in teaching English to pharmacy students, from the teachers' knowledge gap in the pharmaceutical field, big classes, and students' lack of English ability and resources (Solihati & Rahayu, 2020). The research also stated that students mostly learn in middle school and extensively try to improve their English skills independently from various sources.…”
Section: A Related Researchmentioning
confidence: 94%
“…Solihati & Rahayu (2021) stated that the English course covers all areas of English language content. This course cannot be replicated if the teachers do not have adequate knowledge of pharmaceutical terms, as it is one of many problems the teacher faces (Solihati & Rahayu, 2020). Research on higher pharmacy students' needs analysis suggested creating ESP for pharmacy syllabi focused on a certain aspect of academic and developing speaking skills applicable to pharmacy students' future jobs (Poedjiastutie, 2017;Solihati & Rahayu, 2020;Suwandi & Wafa, 2020).…”
Section: A Related Researchmentioning
confidence: 99%
See 1 more Smart Citation